FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELENGKAPAN PEMERIKSAAN IBU HAMIL (ANTENATAL CARE) DI PUSKESMAS KOTA ENDE (Analisis Rekam Medis Tahun 2017) - Fransiska Dominika Riberu; Adeline Lebuan (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Pregnancy examinations are carried out at least 4 (four) times during the pregnancy period whichis carried out 1 (one) time in the first trimester, 1 (One) time in the second trimester, and 2 (Two)times in the third trimester. The purpose of this study was to find out what factors were related tothe completeness of antenatal care at the Ende City Health Center. This study uses cross sectionalquantitative design with retrospective approach which means using secondary data taken frommaternal medical record data that conducted antenatal care visits at Ende City Health Centerfrom January to December 2017. The samples in this study were 103 maternal medical recordsgiving birth who had a pregnancy check up at the Ende City Health Center. The samplingtechnique is total sampling. The results of this study indicate that there is no relationship betweenage (p = 0.061), education (p = 0.733), occupation (p = 0.818), parity (p = 0.426) with completeantenatal care (antenatal care). It was concluded that there was no significant relationshipbetween age, education, employment and parity with the completeness of antenatal care. With theresults of these studies, the researcher suggests that the next researcher can add other variablesand use quantitative and qualitative research methods